Determining the suitability of bio-specimens obtained by fine needle aspiration biopsy at a tertiary hospital in Malawi for immunocytochemical assessment - Mulenga, Maurice (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.